2021
DOI: 10.1080/17476348.2021.1960824
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 clinical phenotypes and short-term outcomes: differences between the first and the second wave of pandemic in Italy

Abstract: Objectives: There are no comparative studies between patients belonging to the first and second waves of the SARS-CoV-2 pandemic, the virus triggering coronavirus disease 2019 (COVID-19). In this retrospective observational study, we analyzed the clinical characteristics and the short-term outcomes of two groups of laboratory-confirmed COVID-19 patients with moderate-to-severe acute respiratory distress syndrome (ARDS) belonging to two different waves of the pandemic. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 30 publications
(30 reference statements)
1
13
0
Order By: Relevance
“…During the second wave, patients were younger, with fewer concomitant chronic conditions and a milder clinical presentation. Short-term clinical outcomes were better, with lower mortality rates and more transfers to a general ward [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…During the second wave, patients were younger, with fewer concomitant chronic conditions and a milder clinical presentation. Short-term clinical outcomes were better, with lower mortality rates and more transfers to a general ward [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…In different countries, a shift has been reported among patients infected with SARS-CoV-2 towards those younger and with fewer comorbidities, with a lower proportion of patients requiring oxygen therapy, a shorter length of hospital stay and lower mortality risk as the pandemic evolved. Most of these studies, however, include case-mixes from medical wards and critical care units, where the range of fatality rates was considerably different and thereby potential selection biases could have been present [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…An Italian study reported that patients in the first wave were more frequently affected by multiple chronic diseases [ 8 ]. We reported that in Tabasco, Mexico, patients admitted in the third wave had a higher number of comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has been suggested that the phenotypic difference in hospitalized patients are related to the variants associated with different stages (or waves) of the COVID-19 pandemic [ 8 ]. A difference in behavior between pandemic waves has recently been reported, where the third wave reported in Spain involved less use of mechanical ventilation and, as a consequence, lower incidence of nosocomial infections, complications, length of stay in the ICU, and mortality [ 9 ].…”
Section: Introductionmentioning
confidence: 99%